2021
DOI: 10.31603/pharmacy.v7i2.5283
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: POTENTIAL OF RED BETEL LEAVES (Piper crocatum) AS ANTI-INFLAMMATORY IN Rheumatoid Arthritis

Abstract: Indonesia is a country with fertile soil and rich in plant species. Currently in society the use of medicinal plants as herbal treatment has increased. Elderly people often experience Rheumatoid Arthritis, which is inflammation of the synovial lining of the joints. One of the plants used by the community is red betel leaf (Piper crocatum). However, scientific information related to the potential of red betel as an anti-inflammatory in Rheumatoid Arthritis is still not widely known by the public. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results obtained meet the specifications for toner preparations. (Aisyiyah et al, 2021) reported that a good standard of viscosity for facial toner is <5 cPs. Viscosity measurement using a viscometer using spindle number 1 with a speed of 60 rpm…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained meet the specifications for toner preparations. (Aisyiyah et al, 2021) reported that a good standard of viscosity for facial toner is <5 cPs. Viscosity measurement using a viscometer using spindle number 1 with a speed of 60 rpm…”
Section: Resultsmentioning
confidence: 99%
“…Red betel leaf (Piper crocatum) contains 4.2% essential oil which mainly consists of betephenol which is an isomer of euganol, allypyrocatechin, cineole-methyleuganol, caryophyllene (sisquiterpenes), kavicol, kavibecol, estragole, and terpinene (Andayani et al, 2014). Red betel leaves (Piper crocatum) contain flavonoids, alkaloids, tannins and essential oils which are thought to be used as antimicrobials (Aisyiyah et al, 2021) Betel leaves have antibacterial activity against Propionibacterium acnes at concentrations of 10%, 15%, 20% and 25%. Red betel leaves have antibacterial activity against Propionibacterium acnes at the minimum inhibitory concentration value of the ethanol extract of red betel leaves at a concentration of 10%.…”
Section: Introductionmentioning
confidence: 99%
“…One of the secondary metabolite compounds contained in H. tuna is flavonoids (Table 1). Aisyiyah et al (2021) argued that flavonoids could regulate the transcription factor NF-kB in the expression of TNF-a . The regulatory process inhibits the secretion of the proinflammatory cytokine TNFa .…”
Section: In Vitro Anti-arthritic Activity Using Denaturation Bsa (Bov...mentioning
confidence: 99%